Defined neurofilament, tau, and beta-amyloid precursor protein epitopes distinguish Alzheimer from non-Alzheimer senile plaques. - Arai, H (1990)
Eight antisera and one monoclonal antibody to synthetic peptides that corresponded to domains extending over the entire length of the beta-amyloid precursor protein (beta-APP), and an antiserum to the full-length 695-amino acid form of the beta-APP, were raised to probe the composition of the core and corona of senile plaques (SPs). We localized distinct beta-APP domains, including the beta-amyloid protein or A4 region, within the SPs of 13 end-stage Alzheimer disease (AD) and 13 age-matched control samples of hippocampus and entorhinal cortex. The composition of SPs also was probed with antibodies to defined epitopes in tau (tau) as well as the large and mid-size neurofilament (NF) proteins. The most important observations were that beta-APP domains outside the A4 region were largely restricted to SP coronas in the AD samples, together with tau and NF determinants, whereas the same epitopes were absent from A4-positive blood vessels and exceptionally rare in non-AD SPs. Indeed, samples from a subset of the non-AD cases contained a considerable number of A4-positive SPs totally devoid of any of the other beta-APP, tau, and NF epitopes. These observations suggest that the deposition of the A4 protein in AD SPs results from the local processing of beta-APPs in association with tau and NF protein fragments. It is unclear whether this association is fortuitous or linked by common mechanisms. However, differences between the complement of beta-APP, tau, and NF protein epitopes in AD versus non-AD brains implicate a defect involving one or more steps in the posttranslational modification, degradation, or elimination of these proteins in AD brains, and this may account for the massive numbers of SPs that characterize AD.